The effect of climate on tourist comfort in Sawa Lake - Prof. Dr. Makki Abd Majeed Al-Rubaie, Ali Khazaal Jawad Al - Kulabi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Climate is one of the variables that influence human health and comfort, and studies show that regions with slight temperature difference encourage people to overcome their laziness and lethargy and engage in inactive behaviour. Moreover, the changing climate requires joint physical and mental activity. Some studies indicate a relationship between efficiency in completing employment or engaging in tourism activities and temperature. Efficiency decreases by 57 percent as the temperature drops below zero, and efficiency approaches 25 percent as the temperature drops below zero (from 10 to 10 degrees). When it comes to work or activity, when the level of work or activity falls to zero percent, the level of work or activity drops to zero percent and when the temperature is 40°C and above 30°C, human efficiency is 75 percent, but when the temperature is 20°C, the human efficiency is 100 percent. As a result, the temperature has an effect, since a temperature rise from 10 ° C to 20 ° C does not have any effect on a person's mood, but a one degree rise in temperature above 40 ° C causes it to rise in summer. In the light of the foregoing, what is the effect of climate on the efficiency and activities of tourists, including tourism activity, with rising temperatures?